Bullying in times of ICT - Rodriguez, Adriana Maria Ortega; Abdullah, Haslinda; Krauss, Steven Eric (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Bullying is detrimental for school climate and a threat to students & teachers’ safety and a threat to positive youth development. The empirical data available indicates that bullying is a worldwide problem faced by many young people either inside or outside school grounds, at work and in their communities. According to the world health organization Bullying constitute an alarming public health and social issue that warrants attention from teachers, health care providers, policy makers, and families. Nonetheless, bullying remains neglected as a social and health issue in most developing countries. The available empirical data indicates that bullying and delinquency are positively associated. Bullying has also been linked to depression, anxiety, psychosomatic complaints, low self-esteem, and poor social functioning among children and adolescences. Likewise, bullying is associated to suicide and suicidal attempts among children and youth. An important and perhaps more detrimental form of bullying have emerged with the rapid development and easy access to information technology and mass media communication: Cyberbullying. This new type of bullying is done using the Internet, mobile devices and ICT in a negative way to indirectly or directly attack or harm another person. The invincibility and anonymity of cyber bullies have made it difficult to manage within the school system and opens the door for more youth to take part in this type of behavior. As the ‘traditional’ bullying, cyber bullying has serious and shocking consequences.